1999
DOI: 10.1109/66.744531
|View full text |Cite
|
Sign up to set email alerts
|

Strategy and metrics for wafer handling automation in legacy semiconductor fab

Abstract: We present a systematic approach for converting a legacy wafer fab from manual wafer handling to fully automatic wafer handling. Our strategy began by quantifying the need for automation in terms of impact on die yield, identifying a seven percent die loss associated with scratches from wafer handling. We then addressed the fundamental changes in production equipment and processes as well as overall fab goals and attitudes that are required to achieve full wafer handling automation. After considering several a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…When products are unique in nature, special techniques for product creation are needed and applied as necessary. When the innovation becomes more emphasized research has shown that lot moves are a more effective metric [21]. No wonder the unfettered application of HVSF metrics to MT-HMLV facilities is so problematic We continue our literature review with this understanding and a drive to find value in the metrics literature and practice.…”
Section: Literature Reviewmentioning
confidence: 92%
See 2 more Smart Citations
“…When products are unique in nature, special techniques for product creation are needed and applied as necessary. When the innovation becomes more emphasized research has shown that lot moves are a more effective metric [21]. No wonder the unfettered application of HVSF metrics to MT-HMLV facilities is so problematic We continue our literature review with this understanding and a drive to find value in the metrics literature and practice.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Many researchers have noted the differences between product and process metrics [21]. Others have noted the differences between continuous processes (i.e.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…반도체용 실리콘 웨이퍼도 최근까 지 로봇 핸드에 의해 낱장 방식으로 직접적으로 표면 접촉이 불가피하게 이루어져오고 있었다. 특히 반도체 공정을 통하여 빈번하게 적재(loading)와 양하(unloading)하는 과정에서 발생 하는 표면 오염과 스크래치 손상과 같은 문제는 수율 향상을 이루어 원가절감을 확보하는데 걸림이 되고 있는 실정이다 (1,2) . 현재 높은 수율을 위해 웨이퍼 직경이 300mm(11.8 in) 이상으로 확대되고 이에 따른 접촉식이 가지는 근본적인 문제를 해결하 기 위하여 비접촉 방식으로 웨이퍼 공정품을 취급 및 이송하는 기술과 방법들이 다양하게 개발되고 있다 (3) .…”
Section: 서 론unclassified
“…The surface of wafers is often accompanied by scratching and contaminating. So contact handling often lead to defective products [1]. In order to improve quality, the traditional handling method obviously can not meet the demands, so in order to avoid contact between handling devices and work pieces, non-contact handling equipment involving magnetic, electrostatic, nearfield and pneumatic levitation entered the life of people.…”
Section: Introductionmentioning
confidence: 99%